ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SPLDV DITINJAU DARI PEMAHAMAN KONSEP SISWA DI KELAS VIII SMP NEGERI 1 TOMA - Hulu, Ester Santi; Welli Siswanti (Universitas Nias Raya, 2024)
The research was prompted by students' frequent errors in solving word problems related to SPLDV material, which adversely affect their grasp of mathematical concepts. The primary objective of this study is to elucidate students' errors in solving story problems based on SPLDV material, focusing on their conceptual understanding. Employing qualitative research methods with a descriptive approach, the research involved 21 eighth-grade students at SMP Negeri 1 Toma during the 2023/2024 academic year. Data were collected through tests and interviews, and subsequent analysis included data reduction, data presentation, and drawing conclusions. The findings indicate that students' conceptual understanding of solving SPLDV story problems is moderately classified. Specifically, the high conceptual understanding category comprises 19% (4 individuals), the medium conceptual understanding category encompasses 57% (12 individuals), and those with a low conceptual understanding constitute 24% (5 individuals). In summary, students with a high conceptual understanding are proficient in comprehending and solving SPLDV story problems. Those in the medium category make errors due to suboptimal conceptual understanding, while those in the low category commit errors in concepts, principles, and operations, rendering them unable to solve mathematical problems presented in story form. The researcher suggests that, recognizing the significance of story problem material in mathematics, teachers should intensify the application of story problem learning, incorporating more diverse models to enhance students' conceptual understanding and foster increased motivation in approaching these problems.